Phenolic Resins: A Century of Progress - Pilato, Louis; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
With global capacity in excess of 5 million tons annually, phenolic resins are one of the leading thermosetting resins that are used in many diverse industries such as wood adhesives, fiberglass/mineral wool binder, molded materials for autos/electronic/electrical industries, brakes, abrasives, foam, coatings/adhesives, laminates, composites, metal castings/refractories, and rubber industry. These phenolic resin business areas are critical to the national economy and general welfare of emerging and developed nations. Although phenolic resins are barely noticed in these applications, it is difficult to imagine their absence since they are vital and not easily replaced by other polymeric materials due to favorable cost/performance characteristics of phenolic resins. In this new book these application areas are summarized and updated by global phenolic experts that are engaged daily in these activities. Further new technology and application areas of global technical activity are presented and include nanotechnology, updated phenolic resin chemistry, carbon fiber and long glass fiber reinforced molding materials, new analyses/testing, carbon foam, carbon/carbon brakes for autos, photo resists, new fiber reinforced systems, renewable raw materials, and recycling. It is anticipated that the new book will feature a global perspective of phenolic resins through the participation of international (North America, Europe and Asia) phenolic experts that was lacking in all previous books related to phenolic resins.
Raw Materials -- Phenols -- Formaldehyde -- Resin Chemistry -- Analyses/Testing -- Production -- Resole Production -- Novolak Production -- Applications -- Wood Composite Adhesives -- Foam -- Mineral Wool Insulation Binders -- Laminates -- Composites -- Abrasives -- Friction -- Photoresists -- Phenolic Molding Compounds -- Alkyl Phenol Resins in Adhesive and Rubber Applications -- Foundry -- Phenolic Resin for Refractories -- Recycling -- Future Aspects.
Keywords: Chemistry; Chemistry, Organic; Polymers; Chemicals -- Safety measures; Chemical engineering; Nanotechnology; Chemistry; Polymer Sciences; Nanotechnology; Condensed Matter Physics; Industrial Chemistry/Chemical Engineering; Safety in Chemistry, Dangerous Goods; Organic Chemistry